Influence of dual-frequency combination on the quality improvement of ultrasound tomography. (March 2016) - Tran, Quang-Huy; Tran, Duc-Tan; Huynh, Huu Tue; Ton-That, Long; Nguyen, Linh-Trung
The most useful feature of ultrasound tomography founded on the inverse scattering theory is that it can detect small structures below the wavelength of the pressure wave. A popular method introduced in ultrasound tomography is the Distorted Born Iterative Method (DBIM). Recently, the dual-frequency combination technique has been utilized to improve the reconstruction quality and increase the convergence rate of the DBIM. This method uses two frequencies, f 1 (low) and f 2 (high), to estimate the sound contrast inN f 1 andN f 2 iterations, respectively. However, the influence of these iteration parameters on the overall performance of the system is not yet known. In this paper, it is shown by using the simulation technique that if we do not pay attention to the choice of these parameters, the reconstruction quality might be worse than that using a single frequency. Furthermore, we focus on the best way to select the parameters in order to improve the reconstruction quality of ultrasound tomography. Given a fixed sumN iter ofN f 1 andN f 2, simulation results show that the best value ofN f 1 isN iter /2; this choice of parameters offers a normalized error that reduces by 67.6%, compared to the conventional DBIM using a single frequency.